Impact of bio-processing treatments on the nutritional and anti-diabetic enzyme inhibitory properties of black wheat, barnyard millet, and black soybean - Goel, Krati; Kushwaha, Archana; Dutta, Anuradha; Sharma, Satish Kumar; Shahi, Navin Chandra; Joshi, Dinesh Chandra; Bhartiya, Anuradha; Gupta, Pranshi (Frontiers in Nutrition, 2025)
ObjectiveThe present study assessed the impact of different bio-processing treatments on the in vitro protein digestibility (IVPD) and inhibitory properties against α-amylase and α-glucosidase of whole grains viz. black wheat (BW), barnyard millet (BM), and black soybean (BS) using at initial optimized conditions including soaking and germination.MethodNutritional analysis of grains was done using standard AOAC methods and in vitro models were used for assessing the anti-diabetic properties.ResultsNutritional analysis of the grains revealed significant differences in various parameters. BS having higher levels of moisture, ash, crude protein, crude fat, and physiological energy value compared to BM and BW. Optimization of soaking (0–24 h) and germination (0–72 h) times showed significant improvements in in-vitro protein digestibility (IVPD), trypsin inhibitory activity (TIU/mg), and glycemic index (GI) across all samples. Considering the management of hyperglycemia, BW and BM do not require any prior processing to be utilized for the development of food products. However, for BS, soaking followed by germination for 48 h proved to be an effective processing, that resulted in an IVPD of 68.706% and a GI of 51.03, with a TIU/mg of 23.166. Soaking reduced α-amylase and α-glucosidase inhibition, while germination increased inhibitory activity significantly (p < 0.05).ConclusionThese findings highlighted the potential benefits of incorporating BW, BM, and BS into the diet for enhanced nutrient intake and better management of hyperglycemia considering the GI and inhibitory activity of α-amylase, α-glucosidase, and trypsin enzymes.